Four new enchytraeid species (Enchytraeidae, Annelida) from a Korean mountain (Jeoksangsan) - Dózsa-Farkas, Klára; Nagy, Hajnalka; Felföldi, Tamás; Hong, Yong (Zootaxa, 2022)
In this article, the descriptions of four new enchytraeid species (Enchytraeidae, Clitellata) from Jeoksangsan (Deogyusan National Park, Korea) are presented: Decimodrilus bulbosus sp. n., Fridericia jeoksangsaniensis sp. n., Fridericia sphaericoides sp. n. and Mesenchytraeus globiferus sp. n. Validity of these new species was verified by comparative morphological and molecular taxonomic analyses (based on the ITS region, CO1 and H3 genes). Apart from the new species, 13 other enchytraeid species were recorded in the soil samples of Jeoksangsan. In addition, new reference sequences are provided for the previously described Fridericia seoraksani Christensen & Dózsa-Farkas, 2012.